From Sacred to Marketed: How Economic Value Has Diminished the Meaning of Traditional Cultural Expressions - Marnia Rani; Hos Arie Rhamadhan Sibarani; Anastasia Wiwik Swastiwi; Lia Nuraini; Muhammad Fajar Hidayat (JURNAL AKTA, 2026)
This study examines the challenges in the process of recording Traditional Cultural Expressions (TCEs). TCE recording requires economic value to obtain protection as communal intellectual property. The rejection of the recording of Talam Sehidang (Makan Sehidang Berlima) as a TCE from the Kepulauan Riau Province. This study uses a normative legal research method that analyzes data qualitatively. The study finds that policymakers frequently exclude SWES traditions rich in moral and spiritual significance from legal protection because they perceive such traditions as lacking direct economic value. However, communities and local governments can generate economic value through active cultural preservation after recording. The requirement of economic value hampers the recording of TCEs. This paper proposes an inclusive TCE recording procedure for communal intellectual property. So that TCEs can be legally recognized and then developed by the host community to be economically valuable. It also provides procedural guidance for local communities to protect culturally meaningful expressions through preservation-based approaches. Economic formalism in cultural recording risks disempowering Indigenous communities and reducing heritage to market logic. By restoring philosophical and moral dimensions to legal recognition, cultural policy can promote equity and protect identity. The lack of documentation for ancient TCE and the economic value requirement for TCE recording led to the failure of the recording process. Thus, this research proposes changes to the requirements in the traditional cultural expression recording policy to prioritize philosophical values alongside economic values. The novelty of this study lies in its critique of the TCE recording process, which requires economic value, making it difficult for cultural actors to obtain protection for TCE as communal intellectual property. However, recording can potentially create income for cultural actors by creating activities such as tourism based on traditional cultural expressions.